Negative electrode composite material, preparation method thereof and battery
By using a negative electrode composite composed of porous carbon sphere framework and metal carbide nanoparticles in sodium ion batteries, the problem of insufficient reversible capacity of hard carbon anode and low potential platform is solved, and the capacity and cycle stability of sodium ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411864404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, the reversible capacity and low potential platform capacity of the hard carbon anode are insufficient, making it difficult to meet the performance required by sodium ion batteries in large-scale applications.
A negative electrode composite material is used, which consists of a porous carbon sphere framework and metal carbide nanoparticles. The metal carbide nanoparticles are distributed in the pores of the porous carbon sphere framework, and the metal elements include Group V B elements. This material is prepared by hydrothermal carbonization and high-temperature pyrolysis of the carbon source precursor to form a negative electrode composite material with excellent uniformity and solid structure.
The capacity and cycling stability of sodium ion batteries are significantly improved, the capacity of low-voltage platform is improved, and a stable interface is formed, realizing the rapid charge transfer kinematics at the electrode/electrolyte interface.
Smart Images

Figure CN119764378A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a negative electrode composite material, a preparation method thereof, and a battery. Background Art
[0002] Sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries because of their low cost and naturally abundant sodium resources, as well as a similar rocking-chair working mechanism that can be used for large-scale energy storage system applications. In the past decade, significant progress has been made in the practical application of sodium-ion battery cathodes, including polyanionic compounds, layered oxides, and Prussian analogs. On the anode side, various materials, such as carbonaceous materials, alloy metals, and metal chalcogenides, have been widely explored. However, due to their complex preparation processes and inherent electrochemical defects, most candidate materials show serious defects in large-scale applications. Carbonaceous materials are considered to be the most promising anode materials because of their advantages such as low cost, easy preparation, and good reproducibility. Unlike the successful application of graphite in traditional lithium-ion batteries, the narrow carbon interlayer spacing (0.335nm) and thermodynamic instability of graphite intercalation compounds hinder the insertion of sodium ions. It is currently recognized that graphite cannot be directly used as an anode material for sodium-ion batteries. Hard carbon consists of interlaced graphite microcrystalline layers, abundant micropores, and defects. It has a relatively large interlayer spacing, can store a large amount of sodium ions, and has a large reversible capacity. Because of the increasing demands on batteries, in order to meet the requirements of full batteries in practical applications, hard carbon anodes with high reversible capacity and appropriate low potential platform capacity are urgently needed. Summary of the invention
[0003] In view of this, the present invention is committed to providing a negative electrode composite material and a preparation method thereof and a battery to solve the problem of insufficient reversible capacity and low potential platform capacity of the hard carbon anode in the prior art.
[0004] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:
[0005] The present invention provides a negative electrode composite material, which comprises a porous carbon sphere skeleton and metal carbide nanoparticles; wherein at least part of the metal carbide nanoparticles are distributed in the pores of the porous carbon sphere skeleton;
[0006] The metal element in the metal carbide nanoparticles includes at least one of the Group VB elements.
[0007] Optionally, the metal carbide nanoparticles are vanadium carbide nanoparticles; optionally, based on the total mass of the negative electrode composite material, the content of the metal carbide nanoparticles is 10-30wt%, preferably 10-15wt%; optionally, the particle size of the metal carbide nanoparticles is 10-50nm, preferably 20-30nm.
[0008] Optionally, the particle size of the negative electrode composite material is 50 to 500 nm, preferably 100 to 200 nm; Optionally, the specific surface area of the porous carbon sphere skeleton is 5 to 10 m 2 / g, preferably 5 to 7 m 2 / g; Optionally, the pore size of the porous carbon sphere skeleton is ≤50nm.
[0009] A second aspect of the present invention provides a method for preparing a negative electrode composite material, the preparation method comprising the following steps:
[0010] S1, performing a first mixing process on a metal source, a modifier and a first solvent to obtain a first solution; performing a second mixing process on a carbon source precursor and a second solvent to obtain a second solution; performing a third mixing process on the first solution and the second solution to obtain a mixed solution;
[0011] S2, subjecting the mixed material to hydrothermal carbonization to obtain a carbonized material; centrifugally washing the carbonized material and then subjecting it to a first drying treatment to obtain a first material;
[0012] S3, mixing the first material and the pore-forming agent solution and performing freeze-drying treatment to obtain a second material; performing a first calcination treatment and a second calcination treatment on the second material in an inert atmosphere to obtain the negative electrode composite material;
[0013] Wherein, the metal element in the metal source includes at least one of the Group VB elements.
[0014] Optionally, the metal source is a vanadium source; preferably, the vanadium source includes at least one of sodium metavanadate, vanadium pentoxide, vanadium dioxide, vanadium chloride and vanadium sulfate; and / or, the carbon source precursor includes at least one of xylose, fructose, sucrose and starch; and / or, the modifier includes at least one of oxalic acid, citric acid and acetic acid, preferably oxalic acid; and / or, the pore former in the pore former solution includes at least one of oxalic acid, salicylic acid, ammonium hydrogen oxalate and ammonium bicarbonate, preferably oxalic acid; the solvent used in the pore former solution is water; and / or, the first solvent is water; and / or, the second solvent is water.
[0015] Optionally, in the first solution, the concentration of the metal element is 0.1-0.2 mol / L, and the concentration of the modifier is 0.2-0.6 mol / L; in the second solution, the concentration of the carbon source precursor calculated as monosaccharide is 0.3-0.5 mol / L; the volume ratio of the first solution and the second solution is (1-2):(1-2); the concentration of the pore-forming agent solution is 0.5-1.5 mol / L; the mass volume ratio of the first material and the pore-forming agent solution is 1 g:(20-50) mL.
[0016] Optionally, the hydrothermal carbonization treatment is performed in a closed high-pressure environment; and / or the temperature of the second calcination treatment is higher than the temperature of the first calcination treatment.
[0017] Optionally, in step S1, the conditions of the first mixing treatment include: temperature of 60-90°C, time of 5-10h, and rotation speed of 300-500rpm; the conditions of the second mixing treatment include: temperature of room temperature, time of 1-2h, and rotation speed of 300-500rpm; the conditions of the third mixing treatment include: temperature of room temperature, time of 1-2h, and rotation speed of 300-500rpm; and / or, in step S2, the conditions of the hydrothermal carbonization treatment include: temperature of 180-200°C, The time is 12 to 24 hours; the conditions for the first drying treatment include: a temperature of 60 to 90°C and a time of 6 to 18 hours; and / or, in step S3, the conditions for the freeze-drying treatment include: a temperature of -60 to -40°C and a time of 24 to 48 hours; the inert atmosphere includes at least one of nitrogen, argon and helium; the conditions for the first calcination treatment include: a temperature of 450 to 550°C and a time of 1 to 2 hours; the conditions for the second calcination treatment include: a temperature of 1000 to 1400°C and a time of 1 to 2 hours.
[0018] Optionally, the preparation method further comprises cooling the material obtained by the second calcination treatment, followed by washing and a second drying treatment.
[0019] A third aspect of the present invention provides a battery, the battery comprising a negative electrode active material, wherein the negative electrode active material comprises the negative electrode composite material described above and / or the negative electrode composite material prepared according to the above preparation method.
[0020] Through the above technical solution, the beneficial technical effects of the present invention are:
[0021] (1) The negative electrode composite material of the present invention comprises a porous carbon sphere skeleton and metal carbide nanoparticles. The material has excellent uniformity and solid structure, which is beneficial to the bulk density of the electrode material and maintains the structural integrity of the electrode during repeated charge and discharge cycles, and can significantly improve the capacity and cycle stability of the sodium ion battery.
[0022] (2) The preparation method of the negative electrode composite material of the present invention prepares porous carbon spheres modified with metal carbide nanoparticles by hydrothermal carbonization and high-temperature pyrolysis of carbon source precursors. During the heating and decomposition process, CO2 decomposed by the modifier can generate an open pore structure by effectively etching amorphous carbon. During the secondary calcination process, the carbon layer of the material is rearranged at high temperature and transformed into a closed-pore structure, which effectively improves the sodium storage platform capacity; at the same time, the porous carbon spheres modified with metal carbide nanoparticles have sufficient pseudo-graphite domains, which can significantly improve the low-voltage platform capacity of sodium ion batteries. The negative electrode composite material synthesized by this method has a stable interface, forms a tight and thin SEI layer, and realizes the fast charge transfer kinetics at the electrode / electrolyte interface.
[0023] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0025] Figure 1 Shown is a SEM image of the negative electrode composite material prepared in Example 1.
[0026] Figure 2 Shown is the HRTEM image of the negative electrode composite material prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention discloses a negative electrode composite material and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0028] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0029] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0032] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0033] In order to solve the problem of insufficient reversible capacity and low potential platform capacity of hard carbon anode in the prior art, the present invention adopts the following technical solution:
[0034] The present invention provides a negative electrode composite material, which comprises a porous carbon sphere skeleton and metal carbide nanoparticles; wherein at least part of the metal carbide nanoparticles are distributed in the pores of the porous carbon sphere skeleton;
[0035] The metal element in the metal carbide nanoparticles includes at least one of the Group VB elements.
[0036] The negative electrode composite material of the present invention comprises a porous carbon ball skeleton and metal carbide nanoparticles. The material has excellent uniformity and solid structure, is beneficial to the bulk density of the electrode material and maintains the structural integrity of the electrode during repeated charge and discharge cycles, and can significantly improve the capacity and cycle stability of the sodium ion battery.
[0037] In a preferred embodiment of the present invention, the metal carbide nanoparticles are vanadium carbide nanoparticles. Vanadium carbide nanoparticles help to increase the content of pseudo-graphite domains in porous carbon spheres, thereby significantly improving the low-voltage platform capacity of sodium ion batteries.
[0038] According to the present invention, based on the total mass of the negative electrode composite material, the content of the metal carbide nanoparticles can be 10-30wt%. In the present invention, the appropriate content of metal carbide nanoparticles is conducive to the performance of gram capacity, improves gram capacity, and at the same time builds a stable interface, forms a tight and thin SEI layer, and realizes the fast charge transfer dynamics on the electrode / electrolyte interface. Exemplarily, based on the total mass of the negative electrode composite material, the content of the metal carbide nanoparticles can be any value among 10wt%, 15wt%, 20wt%, 25wt% and 30wt% or any value within the range of any two of the above values. In the present invention, if the content of metal carbide nanoparticles is too high, it may cause the negative electrode composite material to have a large volume change during the charge and discharge process, and the side reactions will also increase, affecting the long cycle life; if the content of metal carbide nanoparticles is too low, it may not have the effect of improving gram capacity. Preferably, based on the total mass of the negative electrode composite material, the content of the metal carbide nanoparticles can be 10-15wt%;
[0039] According to the present invention, the particle size of the metal carbide nanoparticles may be 10 to 50 nm. In the present invention, the particle size of the appropriate metal carbide nanoparticles has the effect of alleviating volume changes, shortening the ion transmission path, and enhancing the technical effect of material cycle performance. Exemplarily, the particle size of the metal carbide nanoparticles may be any value among 10 nm, 20 nm, 30 nm, 40 nm and 50 nm or any value within the range of any two of the above values. In the present invention, if the particle size of the metal carbide nanoparticles is too large, it may cause the material transmission path to be extended, the ion transmission rate to decrease, and the cycle performance to deteriorate; if the particle size of the metal carbide nanoparticles is too small, it may cause the side reactions of the negative electrode composite material to increase and the coulomb efficiency to decrease. Preferably, the particle size of the metal carbide nanoparticles may be 20 to 30 nm.
[0040] According to the present invention, the particle size of the negative electrode composite material is 50 to 500 nm. In the present invention, the particle size of the suitable negative electrode composite material can effectively reduce the ion transmission path, accelerate the ion transmission rate, and improve the cycle performance. Exemplarily, the particle size of the negative electrode composite material can be any value among 50nm, 100nm, 200nm, 300nm, 400nm and 500nm or any value within the range of any two of the above values. In the present invention, if the particle size of the negative electrode composite material is too large, it may cause the transmission path of the negative electrode composite material to be extended, the ion transmission rate to decrease, and the cycle performance to deteriorate; if the particle size of the negative electrode composite material is too small, it may cause the negative electrode composite material to have an increased side reaction and a reduced coulombic efficiency. Preferably, the particle size of the negative electrode composite material can be 100 to 200nm.
[0041] The porous carbon sphere skeleton in the present invention can provide a continuous conductive framework, and the good mechanical properties can shorten the transmission distance during ion and electron transmission. The stable interface helps to generate a dense SEI layer, so that the battery has good cycle stability and improves the overall electrochemical performance of the electrode.
[0042] According to the present invention, the specific surface area of the porous carbon sphere skeleton is 5 to 10 m 2 / g. Exemplarily, the specific surface area of the porous carbon sphere skeleton can be 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g and 10m 2 / g or any value within the range of values formed by any two of the above values. In the present invention, if the specific surface area of the porous carbon sphere skeleton is too large, it may lead to an increase in the contact area with the electrolyte, an increase in side reactions, and a deterioration in the coulombic efficiency and cycle life; if the specific surface area of the porous carbon sphere skeleton is too small, it may lead to a small contact area with the electrolyte, a reduction in the ion path, an increase in material polarization, and a decrease in cycle performance. Preferably, the specific surface area of the porous carbon sphere skeleton can be 5 to 7 m 2 / g.
[0043] In the present invention, in order to avoid contact between the electrolyte and the inner surface of the pore diameter, SEI is produced. The pore diameter of the porous carbon sphere skeleton is ≤50nm. Exemplarily, the pore diameter of the porous carbon sphere skeleton can be any value among 1nm, 10nm, 20nm, 30nm, 40nm and 50nm or any value within the range of any two of the above values.
[0044] A second aspect of the present invention provides a method for preparing a negative electrode composite material, the preparation method comprising the following steps:
[0045] S1, performing a first mixing process on a metal source, a modifier and a first solvent to obtain a first solution; performing a second mixing process on a carbon source precursor and a second solvent to obtain a second solution; performing a third mixing process on the first solution and the second solution to obtain a mixed solution;
[0046] S2, subjecting the mixed material to hydrothermal carbonization to obtain a carbonized material; centrifugally washing the carbonized material and then subjecting it to a first drying treatment to obtain a first material;
[0047] S3, mixing the first material and the pore-forming agent solution and performing freeze-drying treatment to obtain a second material; performing a first calcination treatment and a second calcination treatment on the second material in an inert atmosphere to obtain the negative electrode composite material;
[0048] Wherein, the metal element in the metal source includes at least one of the Group VB elements.
[0049] The preparation method of the negative electrode composite material of the present invention prepares porous carbon spheres modified with metal carbide nanoparticles by hydrothermal carbonization and high-temperature pyrolysis of carbon source precursors. During the heating and decomposition process, CO2 decomposed by the modifier can generate an open pore structure from effectively etching amorphous carbon. During the secondary calcination process, the carbon layer of the material is rearranged at high temperature and transformed into a closed-pore structure, which effectively improves the sodium storage platform capacity; at the same time, the porous carbon spheres modified with metal carbide nanoparticles have sufficient pseudo-graphite domains, which can significantly improve the low-pressure platform capacity of the sodium ion battery. The negative electrode composite material synthesized by the method has a stable interface, forms a tight and thin SEI layer, and realizes the fast charge transfer kinetics on the electrode / electrolyte interface.
[0050] In a preferred embodiment of the present invention, the metal source is a vanadium source; preferably, the vanadium source includes at least one of sodium metavanadate, vanadium pentoxide, vanadium dioxide, vanadium chloride and vanadium sulfate.
[0051] Exemplarily, the carbon source precursor includes at least one of xylose, fructose, sucrose and starch.
[0052] Exemplarily, the modifier includes at least one of oxalic acid, citric acid and acetic acid, preferably oxalic acid.
[0053] Exemplarily, the pore former in the pore former solution includes at least one of oxalic acid, salicylic acid, ammonium hydrogen oxalate and ammonium bicarbonate, preferably oxalic acid; the solvent used in the pore former solution is water. In the present invention, the pore former (such as oxalic acid) can generate a closed-cell structure at high temperature while forming pores to obtain a high specific capacity, and at the same time, the material interface structure of the metal-oxygen-carbon bond (such as VOC bond) generates a compact SEI layer, thereby effectively improving the first-cycle coulomb efficiency.
[0054] Exemplarily, the first solvent is water.
[0055] Exemplarily, the second solvent is water.
[0056] According to the present invention, in the first solution, the concentration of the metal element can be 0.1-0.2 mol / L. For example, the concentration of the metal element can be any one of 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L and 0.2 mol / L, or any value within the range of any two of the above values. In the present invention, the concentration of the modifier can be 0.2-0.6 mol / L. For example, the concentration of the modifier can be any one of 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L and 0.6 mol / L, or any value within the range of any two of the above values.
[0057] According to the present invention, in the second solution, the concentration of the carbon source precursor calculated as monosaccharide can be 0.3 to 0.5 mol / L. Exemplarily, in the second solution, the concentration of the carbon source precursor calculated as monosaccharide can be any value among 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L and 0.5 mol / L or any value within the range of any two of the above values.
[0058] According to the present invention, the volume ratio of the first solution and the second solution can be (1-2): (1-2). Exemplarily, the volume ratio of the first solution and the second solution can be any value among 1:2, 1:1, and 2:1, or any value within the range of any two of the above values.
[0059] According to the present invention, the concentration of the pore-forming agent solution may be 0.5 to 1.5 mol / L. For example, the concentration of the pore-forming agent solution may be any one of 0.5 mol / L, 0.75 mol / L, 1 mol / L, 1.25 mol / L and 1.5 mol / L or any value within the range of any two of the above values.
[0060] According to the present invention, the mass volume ratio of the first material to the pore-forming agent solution may be 1 g: (20-50) mL. For example, the mass volume ratio of the first material to the pore-forming agent solution may be any value among 1 g: 20 mL, 1 g: 30 mL, 1 g: 40 mL and 1 g: 50 mL, or any value within the range of any two of the above values.
[0061] According to the present invention, the hydrothermal carbonization treatment is carried out in a closed high-pressure environment. In the present invention, the hydrothermal carbonization treatment can be carried out in an autoclave. Exemplarily, the autoclave can be a 100 mL polytetrafluoroethylene-sealed autoclave.
[0062] In the present invention, the temperature of the second calcination treatment is higher than the temperature of the first calcination treatment. In the present invention, the second material is subjected to two calcination treatments, wherein the first calcination treatment helps to form a six-membered carbon ring plane, preparing for the subsequent growth of pseudo-graphite domains; the second calcination treatment helps to form pores, and can develop the six-membered carbon ring generated in the first calcination into pseudo-graphite domains, thereby improving material properties.
[0063] As an exemplary embodiment of the present invention, in step S1, the conditions of the first mixing treatment may include: a temperature of 60 to 90°C, a time of 5 to 10 hours, and a rotation speed of 300 to 500 rpm; the conditions of the second mixing treatment may include: a temperature of room temperature, a time of 1 to 2 hours, and a rotation speed of 300 to 500 rpm; the conditions of the third mixing treatment may include: a temperature of room temperature, a time of 1 to 2 hours, and a rotation speed of 300 to 500 rpm.
[0064] As an exemplary embodiment of the present invention, in step S2, the conditions of the hydrothermal carbonization treatment may include: a temperature of 180-200°C and a time of 12-24 hours; the conditions of the first drying treatment may include: a temperature of 60-90°C and a time of 6-18 hours.
[0065] As an exemplary embodiment of the present invention, in step S3, the conditions of the freeze-drying treatment may include: a temperature of -60 to -40°C and a time of 24 to 48 hours; the inert atmosphere may include at least one of nitrogen, argon and helium; the conditions of the first calcination treatment may include: a temperature of 450 to 550°C and a time of 1 to 2 hours; the conditions of the second calcination treatment may include: a temperature of 1000 to 1400°C and a time of 1 to 2 hours.
[0066] According to the present invention, the preparation method may further include cooling the material obtained from the second calcination treatment, and then washing and drying the material. The washing liquid of the washing treatment may be water, and the conditions of the second drying treatment may include: a temperature of 60 to 90° C. and a time of 6 to 18 hours.
[0067] A third aspect of the present invention provides a battery, the battery comprising a negative electrode active material, wherein the negative electrode active material comprises the negative electrode composite material described above and / or the negative electrode composite material prepared according to the above preparation method.
[0068] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0069] Example 1
[0070] (1) 1.2 g of sodium metavanadate and 2.5 g of oxalic acid were weighed and dissolved in 50 mL of deionized water, and magnetically stirred at 80° C. for 8 hours to obtain a first solution. 3 g of xylose was dissolved in 50 mL of distilled water and stirred for 30 minutes to obtain a second solution. The first solution and the second solution were mixed and stirred for 2 hours to obtain a mixed solution.
[0071] (2) The mixed solution was placed in a 200 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The black product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain the first material.
[0072] (3) A mixture of 100 mL of 1 M oxalic acid solution and 3 g of the first material was stirred for one hour, then placed in liquid nitrogen and frozen for 30 minutes, and then freeze-dried for 24 hours to obtain a sponge-like second material.
[0073] (4) Take 3g of the second material and put it in a porcelain boat. In a nitrogen atmosphere, the heating rate is 5℃ / min, the calcination temperature is 500℃ (oxalic acid high temperature decomposition), the heat preservation time is 2 hours, and then the temperature is raised to 1300℃, the heating rate is 5℃ / min, and the secondary calcination (carbon atoms are rearranged to form closed pores) is carried out. Finally, it is cooled to 500℃ at a cooling rate of 5℃, and then naturally cooled to room temperature. The cooled material is washed with deionized water 3 times and dried to obtain the negative electrode composite material of this embodiment. The SEM image of the negative electrode composite material in this embodiment is as follows: Figure 1 As shown in the HRTEM image Figure 2 shown.
[0074] Example 2
[0075] (1) 1.6 g of vanadium chloride and 2.5 g of oxalic acid were weighed and dissolved in 50 mL of deionized water, and magnetically stirred at 80° C. for 8 hours to obtain a first solution. 3.15 g of fructose was dissolved in 50 mL of distilled water and stirred for 30 minutes to obtain a second solution. The first solution and the second solution were mixed and stirred for 2 hours to obtain a mixed solution.
[0076] (2) The mixed solution was placed in a 200 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The black product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain the first material.
[0077] (3) A mixture of 100 mL of 1 M oxalic acid solution and 3 g of the first material was stirred for one hour, then placed in liquid nitrogen and frozen for 30 minutes, and then freeze-dried for 24 hours to obtain a sponge-like second material.
[0078] (4) Take 3 g of the second material and place it in a porcelain boat. In a nitrogen atmosphere, heat up at a rate of 2°C / min, calcine at a temperature of 500°C (high-temperature decomposition of oxalic acid), and keep warm for 2 hours. Then heat up to 1300°C at a heating rate of 5°C / min, perform secondary calcination (carbon atoms rearrange to form closed pores), and finally cool to 500°C at a cooling rate of 5°C. Then naturally cool to room temperature. The cooled material is washed three times with deionized water and dried to obtain the negative electrode composite material of this embodiment.
[0079] Example 3
[0080] (1) Weigh 4.1 g of vanadium sulfate and 2.5 g of oxalic acid and dissolve them in 50 mL of deionized water, and stir them magnetically at 80° C. for 8 hours to obtain a first solution. Dissolve 3.15 g of starch in 50 mL of distilled water and stir for 30 minutes to obtain a second solution. Mix the first solution and the second solution and stir for 2 hours to obtain a mixed solution.
[0081] (2) The mixed solution was placed in a 200 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The black product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain the first material.
[0082] (3) A mixture of 100 mL of 1 M oxalic acid solution and 3 g of the first material was stirred for one hour, then placed in liquid nitrogen and frozen for 30 minutes, and then freeze-dried for 24 hours to obtain a sponge-like second material.
[0083] (4) Take 3 g of the second material and place it in a porcelain boat. In a nitrogen atmosphere, heat up at a rate of 5°C / min, calcine at a temperature of 500°C (high-temperature decomposition of oxalic acid), and keep warm for 2 hours. Then heat up to 1300°C at a heating rate of 5°C / min, perform secondary calcination (carbon atoms rearrange to form closed pores), and finally cool to 500°C at a cooling rate of 5°C. Then naturally cool to room temperature, wash the material with deionized water three times and dry it to obtain the negative electrode composite material of this embodiment.
[0084] Example 4
[0085] (1) 4.1 g of vanadium sulfate and 2.5 g of oxalic acid were weighed and dissolved in 50 mL of deionized water, and magnetically stirred at 80° C. for 8 hours to obtain a first solution. 3.15 g of glucose was dissolved in 50 mL of distilled water and stirred for 30 minutes to obtain a second solution. The first solution and the second solution were mixed and stirred for 2 hours to obtain a mixed solution.
[0086] (2) The mixed solution was placed in a 200 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The black product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain the first material.
[0087] (3) A mixture of 100 mL of 1 M oxalic acid solution and 3 g of the first material was stirred for one hour, then placed in liquid nitrogen and frozen for 30 minutes, and then freeze-dried for 24 hours to obtain a sponge-like second material.
[0088] (4) Take 3 g of the second material and place it in a porcelain boat. In a nitrogen atmosphere, the heating rate is 2°C / min, the calcination temperature is 500°C (high-temperature decomposition of oxalic acid), and the insulation time is 2 hours. Then the temperature is raised to 1300°C at a heating rate of 2°C / min, and a secondary calcination is performed (carbon atoms are rearranged to form closed pores). Finally, the material is cooled to 500°C at a cooling rate of 5°C, and then naturally cooled to room temperature. The material is washed three times with deionized water and dried to obtain the negative electrode composite material of this embodiment.
[0089] Comparative Example 1
[0090] (1) 3.15 g of glucose was dissolved in 50 mL of distilled water and stirred for 30 minutes. The solution was placed in a 100 mL polytetrafluoroethylene sealed high temperature reactor and kept at 180°C for 12 hours. The product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80°C for 10 hours to obtain carbon spheres.
[0091] (2) 1.5 g of carbon ball material was placed in a porcelain boat and calcined in a nitrogen atmosphere at a temperature of 1300° C. and a heating rate of 5° C. / min. The mixture was kept warm for two hours, cooled to 500° C. at a cooling rate of 5° C., and then naturally cooled to room temperature to obtain the negative electrode composite material of this comparative example.
[0092] Comparative Example 2
[0093] (1) 3.15 g of glucose was dissolved in 50 mL of distilled water and stirred for 30 minutes. The solution was placed in a 100 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain a first material.
[0094] (2) A mixture of 100 mL of 1 M oxalic acid solution and 3 g of the first material was stirred for one hour, then placed in liquid nitrogen and frozen for 30 minutes, and then freeze-dried for 24 hours to obtain a sponge-like material No. 2.
[0095] (3) Take 3 g of the second material and put it into a porcelain boat. It is calcined in a nitrogen atmosphere at a temperature of 500 °C and a heating rate of 5 °C / min. The temperature is kept for two hours. The temperature is then raised to 1300 °C at a heating rate of 2 °C / min for secondary calcination (carbon atoms are rearranged to form closed pores). Finally, the material is cooled to 500 °C at a cooling rate of 5 °C and then naturally cooled to room temperature to obtain the negative electrode composite material of this comparative example.
[0096] Comparative Example 3
[0097] (1) Weigh 4.1 g of vanadium sulfate and 2.5 g of oxalic acid and dissolve them in 50 ml of deionized water, and stir them under magnetic force at 80° C. for 8 hours to obtain a first solution. Dissolve 3.15 g of glucose in 50 ml of distilled water and stir for 30 minutes to obtain a second solution. Mix the first solution and the second solution and stir for 2 hours to obtain a mixed solution.
[0098] (2) The mixed solution was placed in a 200 mL polytetrafluoroethylene sealed high temperature reactor and maintained at 180° C. for 12 hours. The black product was separated by centrifugation, washed by centrifugation / washing / redispersion in water and alcohol for three cycles, and dried in an oven at 80° C. for 10 hours to obtain the first material.
[0099] (3) 3 g of the first material was placed in a porcelain boat and calcined at a heating rate of 2°C / min to 1300°C in a nitrogen atmosphere. The temperature was then lowered to 500°C at a cooling rate of 5°C and then naturally cooled to room temperature. The material was washed three times with deionized water and dried to obtain the negative electrode composite material of this comparative example.
[0100] The negative electrode composite material prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was used as the negative electrode active material, carbon black as the conductive agent, and sodium carboxymethyl cellulose as the binder to prepare the negative electrode slurry, and the mixing mass ratio was negative electrode active material: conductive agent: binder = 8:1:1. The negative electrode slurry was applied to the surface of the copper foil to obtain the negative electrode plate. The metal sodium sheet was used as the positive electrode plate of the counter electrode, the glass fiber diaphragm was used as the isolation membrane, and 1.0 mol / L NaPF6 was dissolved in diethylene glycol dimethyl ether to prepare the electrolyte. The negative electrode plate, the isolation membrane, and the positive electrode plate were assembled in the order of impregnation with the electrolyte, and assembled into a CR2032 button battery in an argon glove box.
[0101] The prepared CR2032 button battery was subjected to an electrical performance test. Using a Land battery test system, the prepared button battery was subjected to a constant current charge and discharge test at a current density of XC at 25°C, with a voltage range of 0 to 2V.
[0102] (1) First discharge capacity, first charge capacity, first coulomb efficiency (first efficiency) test:
[0103] Discharge to 0V at a constant current density of 0.1C, record the discharge capacity at this time as the first discharge capacity; then charge to 2V at a constant current density of 0.1C, record the charge capacity at this time as the first charge capacity; first coulomb efficiency = first charge capacity / first discharge capacity*100%. See Table 1 for specific test results.
[0104] Table 1
[0105]
[0106]
[0107] It can be seen from Table 1 that the button-type half-cells containing the negative electrode composite materials prepared in Examples 1 to 4 all have a relatively high initial discharge capacity (over 500 mAh / g) and a first inventory efficiency of over 88%, while the button-type half-cell prepared in Comparative Example 1 has a first discharge capacity of only (261.3 mAh / g) and a first coulombic efficiency of 83.1%.
[0108] (2) Capacity retention rate (cycle performance) test:
[0109] Discharge at constant current to 0V at a current density of 1C, and record the discharge capacity at this time as the first discharge capacity; then charge at constant current to 2V at a current density of 1C; repeat the above charge and discharge cycle for 500 cycles, and record the discharge capacity at the 500th cycle. Capacity retention rate = discharge capacity at the 500th cycle / first discharge capacity*100%. See Table 2 for specific values.
[0110] Table 2
[0111] Current density (1C) Capacity retention rate (%) Example 1 90.8 Example 2 90.2 Example 3 90.3 Example 4 90.6 Comparative Example 1 82.4 Comparative Example 2 84.7 Comparative Example 3 87.3
[0112] It can be seen from Table 2 that after 500 cycles, the button-type half-cells containing the negative electrode composite materials prepared in Examples 1 to 4 all have a high capacity retention rate (greater than 90%), showing excellent cycle stability, while the button-type half-cells containing the negative electrode composite materials prepared in Comparative Examples 1 to 3 have a low capacity retention rate, with Comparative Example 1 having only 82.4%, and poor cycle stability.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode composite material, characterized in that: The negative electrode composite material comprises a porous carbon sphere skeleton and metal carbide nanoparticles; wherein at least part of the metal carbide nanoparticles are distributed in the pores of the porous carbon sphere skeleton; The metal element in the metal carbide nanoparticles includes at least one of the Group VB elements.
2. The negative electrode composite material according to claim 1, characterized in that: The metal carbide nanoparticles are vanadium carbide nanoparticles; Optionally, based on the total mass of the negative electrode composite material, the content of the metal carbide nanoparticles is 10 to 30 wt%, preferably 10 to 15 wt%; Optionally, the particle size of the metal carbide nanoparticles is 10 to 50 nm, preferably 20 to 30 nm.
3. The negative electrode composite material according to claim 1, characterized in that: The particle size of the negative electrode composite material is 50 to 500 nm, preferably 100 to 200 nm; Optionally, the specific surface area of the porous carbon sphere skeleton is 5 to 10 m 2 / g, preferably 5 to 7 m 2 / g; Optionally, the pore size of the porous carbon sphere skeleton is ≤50 nm.
4. A method for preparing a negative electrode composite material, characterized in that: The preparation method comprises the following steps: S1, performing a first mixing process on a metal source, a modifier and a first solvent to obtain a first solution; performing a second mixing process on a carbon source precursor and a second solvent to obtain a second solution; performing a third mixing process on the first solution and the second solution to obtain a mixed solution; S2, subjecting the mixed material to hydrothermal carbonization to obtain a carbonized material; centrifugally washing the carbonized material and then subjecting it to a first drying treatment to obtain a first material; S3, mixing the first material and the pore-forming agent solution and performing freeze-drying treatment to obtain a second material; performing a first calcination treatment and a second calcination treatment on the second material in an inert atmosphere to obtain the negative electrode composite material; Wherein, the metal element in the metal source includes at least one of the Group VB elements.
5. The preparation method according to claim 4, characterized in that: The metal source is a vanadium source; preferably, the vanadium source includes at least one of sodium metavanadate, vanadium pentoxide, vanadium dioxide, vanadium chloride and vanadium sulfate; and / or, the carbon source precursor comprises at least one of xylose, fructose, sucrose and starch; and / or, the modifier comprises at least one of oxalic acid, citric acid and acetic acid, preferably oxalic acid; and / or, the pore-forming agent in the pore-forming agent solution comprises at least one of oxalic acid, salicylic acid, ammonium hydrogen oxalate and ammonium bicarbonate, preferably oxalic acid; and the solvent used in the pore-forming agent solution is water; And / or, the first solvent is water; And / or, the second solvent is water.
6. The preparation method according to claim 4, characterized in that: In the first solution, the concentration of the metal element is 0.1-0.2 mol / L, and the concentration of the modifier is 0.2-0.6 mol / L; In the second solution, the concentration of the carbon source precursor calculated as monosaccharide is 0.3-0.5 mol / L; The volume ratio of the first solution and the second solution is (1-2): (1-2); The concentration of the pore-forming agent solution is 0.5 to 1.5 mol / L; The mass volume ratio of the first material to the pore-forming agent solution is 1 g: (20-50) mL.
7. The preparation method according to claim 4, characterized in that: The hydrothermal carbonization treatment is carried out in a closed high-pressure environment; and / or, The temperature of the second calcination treatment is higher than the temperature of the first calcination treatment.
8. The preparation method according to claim 4 or 7, characterized in that: In step S1, the conditions of the first mixing treatment include: temperature of 60-90°C, time of 5-10 hours, and rotation speed of 300-500 rpm; the conditions of the second mixing treatment include: temperature of room temperature, time of 1-2 hours, and rotation speed of 300-500 rpm; the conditions of the third mixing treatment include: temperature of room temperature, time of 1-2 hours, and rotation speed of 300-500 rpm; and / or, In step S2, the conditions of the hydrothermal carbonization treatment include: a temperature of 180-200°C and a time of 12-24 hours; the conditions of the first drying treatment include: a temperature of 60-90°C and a time of 6-18 hours; and / or, In step S3, the conditions of the freeze-drying treatment include: a temperature of -60 to -40°C and a time of 24 to 48 hours; the inert atmosphere includes at least one of nitrogen, argon and helium; the conditions of the first calcination treatment include: a temperature of 450 to 550°C and a time of 1 to 2 hours; the conditions of the second calcination treatment include: a temperature of 1000 to 1400°C and a time of 1 to 2 hours.
9. The preparation method according to claim 4, characterized in that: The preparation method further comprises cooling the material obtained by the second calcination process, and then washing and drying the material.
10. A battery, characterized in that: The battery comprises a negative electrode active material, wherein the negative electrode active material comprises the negative electrode composite material according to any one of claims 1 to 3 and / or the negative electrode composite material prepared according to the preparation method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Method for producing nano-sized vanadium carbide powder
CN104495846A
VC0.75@NPC composite material used for sodium-ion battery cathode as well as preparation and application thereof
CN108511721A
Lithium or sodium ion battery anode material and preparation method thereof
CN108539185A
Reduced graphene oxide-metal carbide composite material and preparation method and application thereof
CN108711612A
Carbon sphere coated cobalt selenide nano-composite material and preparation method and application thereof
CN109935791A